Effect Of Combination Of Organic Fertilizer And Inorganic Fertilizer On The Growth And Production Of Hybrid Corn Of Variety JH37 - Wempi Pangalila; Semuel David Runtunuwu; Edy Fredy Lengkong (Sam Ratulangi University, 2023)
The longer the nutrients in the soil will decrease. Lack of nutrients needed by plants can be overcome by fertilization. Fertilizers used can be in the form of organic fertilizers and inorganic/chemical fertilizers (NPK). This study aims to determine the effect of a combination of organic and inorganic fertilizers on the growth and production of hybrid corn JH37. This study used a randomized block design (RBD) consisting of 12 combinations of organic and inorganic fertilizers. The treatment was repeated 3 times. The treatment factors that were tried were as follows: A0B0 (No Manure, No NPK Fertilizer), A0B1 (No Manure+150 kg/ha NPK), A0B2 (No Manure+200 kg/ha NPK), A0B3 (No Manure+250 kg/ha NPK), A1B0 (10 tonnes/ha of manure + without NPK fertilizer), A1B1 (10 tonnes/ha of manure + 150 kg/ha of NPK), A1B2 (10 tonnes/ha of manure +200 kg/ha of NPK), A1B3 (10 tonnes /ha Manure +250 kg/ha NPK), A2B0 (20 tons/ha Manure + Without NPK Fertilizer), A2B1 (20 tons/ha Manure +150 kg/ha NPK), A2B2 (20 tons/ha Manure +200 kg/ha NPK), A2B3 (20 tonnes/ha of manure +250 kg/ha NPK). The variables observed were: plant growth and production. Plant growth includes plant height measured every 2 weeks starting at 14 days old until the final vegetative phase, leaf length, leaf width, and stem diameter (measured in the late vegetative phase). Production (cob diameter, fresh cob weight, cob dry weight, dry shell weight, and production per hectare were measured after harvest). Data were analyzed using analysis of variance. If the effect of the treatment is obtained, it is continued with the Least Significant Difference Test (LSD) at the 5% level. The results showed that the combination of organic and inorganic fertilizers increased the growth and production of hybrid maize Var. JH37. A dosage of 20 tons/ha of organic fertilizer + 200 kg/ha of the best inorganic fertilizer increases the growth and production of JH37 hybrid corn. Production of hybrid corn var. The highest JH37 was in the A2B3 combination (20 tonnes/ha of manure + 250 kg/ha of NPK), namely 5.48 tonnes/ha. Keywords: organic fertilizer, inorganic fertilizer, growth, and production Abstrak Semakin lama unsur hara pada tanah akan berkurang. Kekurangan unsur hara yang diperlukan oleh tanaman dapat diatasi dengan pemupukan. Pupuk yang digunakan dapat berupa pupuk organik dan pupuk anorganik/kimia (NPK). Penelitian ini bertujuan untuk mengetahui pengaruh kombinasi pupuk organik dan pupuk an organik terhadap pertumbuhan dan produksi jagung hibrida Var. JH37. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK) yang terdiri dari 12 kombinasi pupuk organik dan pupuk anorganik. Perlakuan diulang sebanyak 3 kali. Adapun faktor perlakuan yang dicobakan adalah sebagai berikut : A0B0 (Tanpa Pupuk Kandang, Tanpa Pupuk NPK), A0B1 (Tanpa Pupuk Kandang+150 kg/ha NPK), A0B2 (Tanpa Pupuk Kandang+200 kg/ha NPK), A0B3 (Tanpa Pupuk Kandang+250 kg/ha NPK), A1B0 (10 ton/ha Pupuk Kandang +Tanpa Pupuk NPK), A1B1 (10 ton/ha Pupuk Kandang +150 kg/ha NPK), A1B2 (10 ton/ha Pupuk Kandang +200 kg/ha NPK), A1B3 (10 ton/ha Pupuk Kandang +250 kg/ha NPK), A2B0 (20 ton/ha Pupuk Kandang +Tanpa Pupuk NPK), A2B1 (20 ton/ha Pupuk Kandang +150 kg/ha NPK), A2B2 (20 ton/ha Pupuk Kandang +200 kg/ha NPK), A2B3 (20 ton/ha Pupuk Kandang +250 kg/ha NPK). Variabel yang diamati yaitu : Pertumbuhan tanaman dan Produksi. Pertumbuhan tanaman meliputi tinggi tanaman di ukur setiap 2 minggu dimulai saat berumur 14 hari sampai fase vegetatif akhir, Panjang daun, lebar daun diameter batang (diukur pada fase vegetative akhir). Produksi (Diameter Tongkol, Berat Basah Tongkol, Berat kering tongkol, berat pipil kering dan produksi perhektar diukur setelah panen). Data dianalisis dengan menggunakan analisis ragam. Jika perdapat pengaruh perlakuan dilanjutkan dengan Uji Beda Nyata Terkecil (BNT) pada taraf 5%. Hasil penelitian menunjukkan bahwa kombinasi pupuk organic dan pupuk anorganik meningkatkan pertumbuhan dan produksi jagung hibrida Var. JH37. Dosis 20 ton/ha pupuk organic+200 kg/ha pupuk Anorganik terbaik meningkatkan pertumbuhan dan produksi jagung hibrida JH37. Produksi jagung hibrida var. JH37 tertinggi pada kombinasi A2B3 (20 ton/ha Pupuk Kandang +250 kg/ha NPK) yaitu 5,48 ton/ha. Kata kunci: pupuk organic, pupuk anorganik, pertumbuhan dan produksi jagung hibrida.